What fiscal policy is most effective? A Meta Regression Analysis - Sebastian Gechert (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
We apply meta regression analysis to a unique data set of 104 studies on multiplier effects with 1069 reported multipliers in order to derive stylized facts and to quantify the differing effectiveness of the composition of fiscal impulses, adjusted for the interference of study-design characteristics and sample specifics. As a major result, we find that public spending multipliers are close to one and about 0.3 to 0.4 units larger than tax and transfer multipliers. Public investment multipliers are even larger by approximately 0.5 units. Reported multipliers vary with study-design, thus, policy consulting based on a certain multiplier study should lay open by how much specification affects the results. Our meta analysis provides guidance concerning influential factors, their sign and magnitude.
urn:nbn:de:101:1-201403119027
Keywords: E27; E62; H30; 330; multiplier effects; fiscal policy; meta analysis